2015
DOI: 10.1080/02755947.2015.1044629
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smallmouth Bass Predation on Recruitment of Age‐0 Yellow Perch in South Dakota Glacial Lakes

Abstract: We estimated the influence of predation by Smallmouth Bass Micropterus dolomieu on recruitment of age‐0 Yellow Perch Perca flavescens in two northeastern South Dakota glacial lakes. We estimated a likely range in consumption of age‐0 Yellow Perch using Smallmouth Bass diet information from two time periods when age‐0 Yellow Perch constituted high (2008) and low (2012 and 2013) proportions of Smallmouth Bass diets, and bass population size estimates as inputs in a bioenergetics model. The proportion of age‐0 Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Specifically, Nielsen (1980) suggested that predation of age‐1 and age‐2 Yellow Perch by Walleye was the primary factor influencing changes in ranked abundance of year‐classes and that year‐class strength was likely not fixed until after age‐2 during 1962–1974 in Oneida Lake, New York. Predation of Yellow Perch ages 0–2 by predators including Smallmouth Bass Micropterus dolomieu and Northern Pike Esox lucius has also been documented and, in glacial lakes of South Dakota that are similar to those that were included in our study, age‐0 Yellow Perch comprised 27–42% of Smallmouth Bass diets by weight (Bacula 2009; Dembkowski et al 2015) and Yellow Perch of unspecified ages comprised 30% and 50% of Walleye and Northern Pike diets by weight, respectively (Blackwell et al 1999). If predation results in substantial losses of Yellow Perch at multiple life stages before recruitment to the fishery, relationships between consecutive ages of individual cohorts may become obscured and year‐class strength may not be fixed until after the fish exceed the gape limitations of predators (e.g., Nielsen 1980).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Specifically, Nielsen (1980) suggested that predation of age‐1 and age‐2 Yellow Perch by Walleye was the primary factor influencing changes in ranked abundance of year‐classes and that year‐class strength was likely not fixed until after age‐2 during 1962–1974 in Oneida Lake, New York. Predation of Yellow Perch ages 0–2 by predators including Smallmouth Bass Micropterus dolomieu and Northern Pike Esox lucius has also been documented and, in glacial lakes of South Dakota that are similar to those that were included in our study, age‐0 Yellow Perch comprised 27–42% of Smallmouth Bass diets by weight (Bacula 2009; Dembkowski et al 2015) and Yellow Perch of unspecified ages comprised 30% and 50% of Walleye and Northern Pike diets by weight, respectively (Blackwell et al 1999). If predation results in substantial losses of Yellow Perch at multiple life stages before recruitment to the fishery, relationships between consecutive ages of individual cohorts may become obscured and year‐class strength may not be fixed until after the fish exceed the gape limitations of predators (e.g., Nielsen 1980).…”
Section: Discussionsupporting
confidence: 56%
“…We addressed our objectives using data that were collected from 2000 to 2016 for larval, postlarval age‐0, and adult Yellow Perch as part of multiple complementary research projects that examined the early life history and population dynamics of Yellow Perch in nine glacial lakes in eastern South Dakota (Isermann 2003; Ward et al 2004; Isermann et al 2007; Isermann and Willis 2008; Jansen 2008; Dembkowski et al 2012, 2015, 2016; Dembkowski 2014). The lakes varied in morphometric and physiochemical characteristics, but they were generally shallow and productive systems that are typical of natural lakes in the Prairie Pothole Region of the Northern Great Plains (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In South Dakota glacial lakes, yellow perch constitute a primary prey resource for other sport fishes including walleye and northern pike (Blackwell et al, 1999). Recent evidence also suggests the potential for substantial predation of juvenile yellow perch by smallmouth bass in some South Dakota glacial lakes (Bacula, 2009;Dembkowski et al, 2015), although smallmouth bass abundance was not included as a predictor variable in models tested herein. abundance of potential predators is likely a function of the interplay between predation and density-dependent growth; specifically, predation by walleye and northern pike may release yellow perch from size constraints brought on by density-dependent growth.…”
Section: Discussionmentioning
confidence: 94%
“…Field sampling.-We captured Smallmouth Bass by angling during separate sampling events in July and September 2013 and tagged individual fish to quantify their summer growth, estimate their abundance and size structure, and examine their diet composition within the study reach. Angling is commonly used to sample Smallmouth Bass for diet assessments (e.g., Fayram and Sibley 2000;Dembkowski et al 2015). In both 2-d sampling events, each captured individual was measured (fork length, mm), weighed (g), and then evaluated for stomach contents via gastric lavage (Foster 1977).…”
Section: Methodsmentioning
confidence: 99%